Wagner on Ljubljana's concert and opera stages - Weiss, Jernej (Muzikološki zbornik, 2013)
The contribution presents the most important milestones in Ljubljana's concert and opera stagings of Richard Wagners works. In connection with the programme orientations of the leading music institutions in the 19th and 20th centuries in Slovenia and the concurrent cultural-political changes, it attempts to determine the reasons for the (non)staging of Wagners works and in this way deal with some of the, unfortunately, still existing stereotypes related to Wagners music in Slovenia.
Keywords: Deželno gledališče; Filharmonična družba; koncertni odri; Ljubljana; Opera in balet; operni odri; SNG; Wagner, Richard, 1813-1883